2001
DOI: 10.1093/ps/80.6.753
|View full text |Cite
|
Sign up to set email alerts
|

n-3 Enrichment of Chicken Meat. 2. Use of Precursors of Long-Chain Polyunsaturated Fatty Acids: Linseed Oil

Abstract: To assess the effect of supplying linseed oil (LO) in the diet on performance, fatty acid (FA) composition, and quality objective parameters of broiler meat, diets enriched with 0, 2, or 4% LO plus tallow (T) up to 8% added fat (T1, T2, and T3, respectively) were given to broiler chickens throughout a 38-d growth period. T3 birds were slaughtered at 24 or at 52 d of age to study the effect of feeding time on FA accumulation in tissue. Objective and subjective evaluations of meat quality were performed on sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
91
3
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(135 citation statements)
references
References 23 publications
29
91
3
1
Order By: Relevance
“…It is probable that the performance of this enzymatic system is not sufficient for higher levels. Lopez-Ferrer et al (2001) found out that increasing dietary levels of LNA resulted in an increase in the contents of EPA and DHA in TM; in our experiment, however, this observation for DHA was not corroborated. Our results support the theory that broiler chickens show a limited capacity to desaturate and elongate the chain of LNA (Chanmugam et al, 1992;Lopez-Ferrer et al, 1999).…”
Section: Resultscontrasting
confidence: 93%
See 1 more Smart Citation
“…It is probable that the performance of this enzymatic system is not sufficient for higher levels. Lopez-Ferrer et al (2001) found out that increasing dietary levels of LNA resulted in an increase in the contents of EPA and DHA in TM; in our experiment, however, this observation for DHA was not corroborated. Our results support the theory that broiler chickens show a limited capacity to desaturate and elongate the chain of LNA (Chanmugam et al, 1992;Lopez-Ferrer et al, 1999).…”
Section: Resultscontrasting
confidence: 93%
“…MSM 6215648905). (Olomu and Baracos, 1991;Crespo and EsteveGarcia, 2001;Lopez-Ferrer et al, 2001;Cortinas et al, 2004;Dublecz et al, 2004;Villaverde et al, 2006).…”
mentioning
confidence: 99%
“…Low pH value of meat has been reported to increase shelf-life (Allen et al, 1997). These results are in agreement with Lopez-Ferrer et al (2001) and Poławska et al (2011) who reported that tenderness of PM was not influenced by the addition of FSM to the diet of chickens and emus, respectively. However, Mridula et al (2011) reported that the addition of FSM for up to 150 g/kg diet of broiler chickens did not influence appearance, colour, tenderness or flavor of breast meat.…”
Section: Discussionsupporting
confidence: 89%
“…The fatty acid profile of meat could be altered by adding fish products to the feed for broilers (López-Ferrer et al, 2001a;Cortinas et al, 2004) or vegetable oils (López-Ferrer et al, 2001b;Schneiderova et al, 2007;Zelenka et al, 2008). Similar findings were detected in the present study (Table 3).…”
Section: Discussionsupporting
confidence: 89%
“…to the diet. It has been shown that the content of n-3 PUFA, particularly of α-linolenic acid (ALA,, in poultry meat can readily be improved by increasing the levels of n-3 PUFA in poultry diets through the incorporation of vegetable oils (López-Ferrer et al, 2001b;Schneiderova et al, 2007;Zelenka et al, 2008) or oily fish by-products (López-Ferrer et al, 2001a;Cortinas et al, 2004). However, some authors reported the unpleasant flavour of fish in the meat of broilers fed 1.5% to 2.5% of FO (Hardin et al, 1964).…”
mentioning
confidence: 99%